2020
DOI: 10.2807/1560-7917.es.2020.25.37.2001671
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor: COVID-19 cases among school-aged children and school-based measures in Hong Kong, July 2020

Abstract: We read with interest the recent rapid communication by Stein-Zamir et al. analysing a major outbreak in an Israeli high school, which has been attributed to crowded conditions in classrooms and exemption from wearing face masks [1]. We would like to share our perspective from Hong Kong, where cases among school-aged children have been reported but did not lead to school outbreaks. August Secondary school cluster Case 4 and Case 9 had team sport activity together without wearing a face mask; Case 4 and Case 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…On the contrary, evidence from Rhode Island in the US, noted a very small number of cases after schools reopened during June-July 2020, which the authors attribute to the strict non-pharmaceutical interventions implemented including the use of face masks, physical distancing, screening for symptoms and classroom disinfection (22). A similar experience has been highlighted in Hong Kong, where multiple potential introductions of COVID-19 did not lead to secondary transmission, amidst a setting with numerous precautionary in-school measures, such as widespread facemask use, daily temperature checks, and staggered entries and exits (36).…”
Section: Discussionmentioning
confidence: 60%
“…On the contrary, evidence from Rhode Island in the US, noted a very small number of cases after schools reopened during June-July 2020, which the authors attribute to the strict non-pharmaceutical interventions implemented including the use of face masks, physical distancing, screening for symptoms and classroom disinfection (22). A similar experience has been highlighted in Hong Kong, where multiple potential introductions of COVID-19 did not lead to secondary transmission, amidst a setting with numerous precautionary in-school measures, such as widespread facemask use, daily temperature checks, and staggered entries and exits (36).…”
Section: Discussionmentioning
confidence: 60%
“…Such data has only been used in (family) case cluster studies (e.g. Chan et al 2020 ; Danis et al 2020 ; Fong et al 2020 ). In the context of our study, of particular interest would have been being able to distinguish between the proportion of infections that took place outside the home (more likely among children and people employed) and those within the household (more probable among older people and those living in multigenerational or overcrowded households).…”
Section: Discussionmentioning
confidence: 99%
“…In Hong Kong, 20 confirmed cases of COVID-19 in schoolchildren aged 5to17 were investigated to gain more knowledge about the spread of infection in schools. Through broad school testing and medical monitoring of cases and their close contacts, the study showed that no more cases could be linked to the 20 cases, indicating that the risk of further infectivity in schools is limited (54).…”
Section: The Spread Of Infection In Preschools and Schoolsmentioning
confidence: 98%